Understanding Intellectual Capital in MSMEs Knowledge Management: Bibliometric Analysis and Systematic Literature Review - Fourqoniah, Finnah; Prakasa, Yudha; Bharata, Wira (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Effective and efficient use of resources is the main strategy for the success or resilience of MSMEs. The management of internal resources is believed to be the main factor that supports the existence of MSMEs. Intangible knowledge resources are the most difficult to manage. Several previous studies have tried to reveal the importance of knowledge management. However, there has been no comprehensive discussion regarding the management of MSMEs. The main aim of this research is to comprehensively examine how knowledge management, from an intellectual capital perspective, provides real benefits for MSMEs. To provide a detailed description, we use several analysis methods. Bibliometric analysis, the PRISMA method, and systematic literature observation were used. Our source documents are based on the Scopus database. We found that there are at least 108 documents relevant to this research topic. In general, we see that the number of publications on this topic increases every year. The results of this research provide evidence of the contribution of intellectual capital to various sectors in various countries. The earliest literature we find on this topic comes from Italy and Brazil. We also found that China has contributed the most to the literature related to knowledge management. Apart from that, it is known that Indonesia contributes the most authors to the literature on this topic. Based on cluster analysis in the use of keywords, we can determine the scientific and systematic relationships in each previous literature. In this context, the findings of this research also provide predictions for further research, especially regarding intellectual capital management in MSMEs.